Hadoop‐based framework for big data analysis of synchronised harmonics in active distribution network. Issue 16 (30th August 2017) - Cao, Zijian; Lin, Jin; Wan, Can; Song, Yonghua; Taylor, Gareth; Li, Maozhen
Abstract : Synchronised harmonic analysis that utilises GPS signals to synchronise harmonic measurements enables advanced power quality analysis in smart grid. However, it is difficult to put this promising technology into practice due to an extremely high requirement on data storage and processing. To overcome this problem, this study presents a novel Hadoop‐based framework for big data analysis of synchronised harmonics in distribution networks. The proposed framework facilitates harmonic data processing associated with data storage and advanced analysis based on big data techniques. Under this framework, a big matrix multiplication algorithm based on MapReduce programming model solving the harmonic state estimation problem is deployed in the stage of data processing. A MapReduce‐based harmonics distortion calculation is implemented as an advanced analysis for harmonics. Comprehensive numerical studies are carried out to analyse the characteristics of the proposed algorithm and verify the effectiveness of the proposed framework.